From Painless to Prominent: A Case of A Giant Neck Lipoma (Bangladesh Journal of Medical Science, 2025)
Head and neck lipomas are rare, accounting for less than 5% of all lipomas. They typically present as slow-growing, painless masses but can pose diagnostic challenges due to their proximity to vital structures. We report a case of a 48-year-old female with a gradually enlarging mass in the right lateral neck region mimicking a goitre. Imaging confirmed a well-encapsulated lipoma, and surgical excision was performed. Histopathology verified its benign nature. While prognosis is generally excellent, infiltrating lipomas carry a risk of recurrence. This case highlights the importance of accurate diagnosis and timely surgical management of head and neck lipomas.BJMS, Vol. 24 No. 04 October’25 Page : 1338-1340